A multi‐scale analysis of the extreme rain event of Ouagadougou in 2009. (29th November 2017) - Lafore, Jean‐Philippe; Beucher, Florent; Peyrillé, Philippe; Diongue‐Niang, Aïda; Chapelon, Nicolas; Bouniol, Dominique; Caniaux, Guy; Favot, Florence; Ferry, Frédéric; Guichard, Françoise; Poan, Emmanuel; Roehrig, Romain; et al.
Abstract : This study presents a multi‐scale analysis of an extreme rain event that occurred in Burkina Faso on 1 September 2009 with an absolute record of 263 mm rainfall observed at Ouagadougou. This high‐impact weather system results from the combination of several favourable ingredients at different scales. The sea‐surface temperature anomaly patterns in July–August 2009 of both the Atlantic cold tongue, the Tropical Atlantic Dipole and the Mediterranean Sea are favourable factors for the northward penetration of the West African monsoon. The intense convective activity of the last 10‐day period in August is associated with the crossing of a convectively coupled Kelvin wave increasing the African easterly wave (AEW) activity, and of an equatorial Rossby wave. At the synoptic scale this event corresponds to the passage of a train of three AEWs with increasing magnitude. Behind the first AEW trough axis, an intense and deep southerly monsoon burst develops. It contributes to the amplification of the second AEW and its breaking is associated with the formation of an intense meso‐vortex on the southern flank of the African easterly jet. Compared to the fast‐moving squall line, the dominant type of precipitating weather system over the Sahel, the Ouagadougou precipitating system appears to be a moist vortex propagating slowly, allowing rainfall accumulation, without wind gusts or convective cold pools observed at the surface. The main precipitation area is located about 2° longitude downshear (westward due to the African easterly jet) of the centre of this strong meso‐vortex. Abstract : This Ouagadougou extreme event (263 mm) corresponds to the passage of an African easterly wave train combined with a strong and large wet anomaly initiated over eastern Africa, resulting in its breaking and the formation of a moist vortex forcing intense precipitation. Contrary to squall lines, this system is not associated with density currents and propagates slowly allowing strong precipitation accumulation. At larger scales, interactions between several equatorial waves (Kelvin and Rossby) contributed to the occurrence of this event.